The Rapidly Expanding Family of Human Polyomaviruses: Recent Developments in Understanding Their Life Cycle and Role in Human Pathology - White, Martyn K. (Public Library of Science, 2013)
Since their discovery in 1971, the polyomaviruses JC (JCPyV) and BK (BKPyV), isolated from patients with progressive multifocal leukoencephalopathy and polyomavirus-associated nephropathy, respectively, remained for decades as the only known members of the Polyomaviridae family of viruses of human origin. Over the past five years, the application of new genomic amplification technologies has facilitated the discovery of several novel human polyomaviruses (HPyVs), bringing the present number to 10. These HPyVs share many fundamental features in common such as genome size and organization. Infection by all HPyVs is widespread in the human population, but they show important differences in their tissue tropism and association with disease. Much remains unknown about these new viruses. In this review, we discuss the problems associated with studying HPyVs, such as the lack of culture systems for the new viruses and the gaps in our basic understanding of their biology. We summarize what is known so far about their distribution, life cycle, tissue tropism, their associated pathologies (if any), and future research directions in the field.